HEROISM OF DESMOND DOSS IN’ HACKSAW RIDGE’: A HERO’S JOURNEY - Farennisa Audy Vandia Putri; Ika Oktaria Cahyaningrum (Acceleration: Multidisciplinary Research Journal, 2024)
Heroism is the pinnacle of greatness in human beings, heroes demonstrate the courage to act with moral fortitude and put the needs of others before their own or above their own needs. Many films use the theme of war heroism. Hacksaw Ridge, one of the heroic films which tells the story of Desmond Doss, the heroic warrior. Desmond Doss, the main character. This research aims to analyze how the heroism represented by Desmond and the Hero's Journey experienced by the protagonist. Hero experienced by the main character. The method used in this research This research is descriptive qualitative methods, while the sampling technique used is with purposive sampling method. Data analysis uses data reduction, data display, and conclusions and verification. This research was analyzed with the elements of heroism and the Hero's Journey theory. The theory in question is Joseph Campbell's Hero's Journey theory. The data found were taken by analyzing the scenes in the film which were then validated using theoretical triangulation. The data validation is carried out using theoretical triangulation. Based on research, the author found 32 data on heroic characteristics and 17 data on the Hero's Journey. From these data, it can be concluded that Desmond can be called a hero because he has 5 elements of heroism and he has passed the Hero's Journey phase.